Motivational profiles of prospective mathematics teachers based on different types of personalities - Annisa Dwi Kurniawati; Julia Noviani (Beta: Jurnal Tadris Matematika, 2022)
[English]: Students' motivation and personality are two important aspects of mathematics learning. Both aspects can be used as one of the bases for mathematics educators to design learning strategies. However, students' motivation for different personality types has not been widely revealed. This qualitative research aims to uncover prospective mathematics teachers’ (PMT) motivation with introverted and extroverted personalities in mathematics learning. The participants were selected using a personality test and then an interview was conducted. The findings show that, in general, the motivation profile of introverted PMT is different from the extroverted ones. Past experiences of success and self-efficacy became essential factors in the motivation of the introvert. As for the extrovert, friends, and interactions in an activity become a motivating factor in learning mathematics. Implications of the findings will be further discussed. [Bahasa]: Motivasi dan kepribadian siswa merupakan dua aspek penting dalam pembelajaran matematika. Kedua aspek tersebut dapat dijadikan salah satu landasan bagi pendidik matematika untuk merancang strategi pembelajaran. Namun, bagaimana motivasi siswa berdasarkan tipe kepribadian yang berbeda belum banyak terungkap. Penelitian kualitatif ini bertujuan mengungkap profil motivasi mahasiswa calon guru dengan kepribadian introver dan ekstrover dalam pembelajaran matematika. Partisipan dipilih dengan menggunakan instrumen tes kepribadian, kemudian dilakukan wawancara. Hasil penelitian menunjukkan, secara umum profil motivasi calon guru introver berbeda dengan yang memiliki kepribadian ekstrover. Pengalaman sukses masa lalu dan kepercayaan diri tentang kemampuan diri menjadi faktor penting dalam motivasi calon guru introver. Sedangkan untuk calon guru ekstrover, teman dan interaksi dalam suatu kegiatan menjadi faktor motivasi dalam belajar matematika. Implikasi hasil penelitian ini akan dibahas lebih lanjut dalam artikel ini.